Evidence for Resilient Agriculture Dataset v1.0.1 - Rosenstock, Todd Stuart; Steward, Peter Richard; Shuck, Julia; Richards, Meryl; Poultouchidou, Anatoli; Ombewa, Babra Vivian Adhiambo; Mumo, Elijah Mustoki; Manda, Lucas; Madalinska, Anna; Kamau, Hannah; Kagwiria, Dorcas; Gitau, Angela; et al. (2024)
The Evidence for Resilient Agriculture (ERA v1.0.1) dataset contains112,859 observations from 2,011 agricultural studies conducted in Africa from 1934 to 2018. ERA examines the efficacy of 363 practice combinations on 87 environmental, social, and agricultural-economic outcome indicators. Observations are geolocated and can be linked to opensource environmental, economic, and social data to investigate the interaction of local context on performance indicators. ERA offers a new resource for evaluating the impact of changing farming practices, providing foundational evidence for designing policies, programs, and investments to support African agricultural development.